Efficient multihop transmission scheme for error-free relay forwarding in cooperative networks - James, Ashish (2016)
Multihop cooperative communication is emerging as a key concept to extend the coverage area of the network and potentially increase the capacity. The spectral efficiency of such networks can be improved by adapting the transmission to time-varying channel conditions, referred to as incremental relaying. Although such incremental relaying concepts are progressively being studied, many challenges, such as erroneous transmissions by intermediate nodes and end-to-end delay of the network, limit its practical use due to lack of an efficient implementation. This paper proposes an efficient multihop incremental relaying technique. In this method, erroneous relay forwarding is mitigated, and the overhead for coordination among nodes is reduced by exploiting the implicit feedback channel available due to the broadcast nature of wireless transmissions. The proposed scheme fully leverages the benefit of overhearing and eliminates the additional feedback slots required for validation. Further, it ensures reliable forwarding of information, which optimizes the throughput of multihop networks. Thorough analysis of the proposed scheme is performed under different deployment environments, and the theoretical analyses presented in this paper are supported with results from extensive simulation studies.